2016
DOI: 10.1097/md.0000000000004747
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis of carotid stent from a population-based database in Taiwan

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Primary position. NR Cheng et al (2016) [ 44 ] Taiwan National Health Research Insurance database from 2004 to 2015 AMI, ischemic stroke, hemorrhagic stroke, all cause death AMI: 410; ischemic stroke: 434–437; hemorrhagic stroke: 430–432 (ICD-9). NR NR Chuang et al (2016) [ 45 ] Taiwan National Health Research Insurance database from 1996 to 2011 ACS, ischemic stroke, hemorrhagic stroke ACS: 410, 411; ischemic stroke: 433–438; hemorrhagic stroke: 430–432 (ICD-9).…”
Section: Resultsmentioning
confidence: 99%
“…Primary position. NR Cheng et al (2016) [ 44 ] Taiwan National Health Research Insurance database from 2004 to 2015 AMI, ischemic stroke, hemorrhagic stroke, all cause death AMI: 410; ischemic stroke: 434–437; hemorrhagic stroke: 430–432 (ICD-9). NR NR Chuang et al (2016) [ 45 ] Taiwan National Health Research Insurance database from 1996 to 2011 ACS, ischemic stroke, hemorrhagic stroke ACS: 410, 411; ischemic stroke: 433–438; hemorrhagic stroke: 430–432 (ICD-9).…”
Section: Resultsmentioning
confidence: 99%
“…Although external validation is an essential step in prediction model development, only 4 of the 30 included models had been externally validated in an independent patient population before; 2 were externally validated in the same article in which their development was described (Alcocer 2013 and Cheng 2016), 16 , 17 and the other 2 had each been validated twice in independent validation studies (Rothwell 1999 and Tu 2003). 18 21 Our findings are similar to the findings of these previous studies, except that the discriminative performance of the Tu 2003 and Cheng 2016 models was slightly better in the previous external validations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was indicated that the risk of plaque was significantly greater in people with increased systolic blood pressure (SBP) variability (every 10 mmHg increase) and diastolic blood pressure (DBP) variability (1,24,25). Pulse pressure (PP) variability (every 10 mmHg increase) raises the risk of carotid plaque for both community-based subjects and stroke patients (26,27).…”
Section: Blood Pressurementioning
confidence: 99%